The Influence of Marital Adjustment and Family Function toward Family Strength in Early Marriage - Dita Septia Ningsih; Tin Herawati (Journal of Family Sciences, 2017)
Aim of this study is to examine the influence of marital adjustment and family function toward family strength in early marriage. Research was located in Cibeber II village and Karehkel village, Leuwiliang sub-district, Bogor district, West Java. Samples of this study are 60 mothers from an early marriage family (under 20 years old) whose children are under five years old, and willingly participate in this study. Samples were chosen purposively. There is of correlation showed that age of husbands and age of husbands when married were negative significant correlation with family strength. Income per capita, marital adjustment, and family function were positive significant with family strength. The factors that affect family strength are income per capita, marital adjustment, and family function